Promoting stress-tolerant varieties at scale through agricultural insurance and advisories – A randomized trial in Kenya - Kramer, Berber (2019)
Agricultural productivity in Africa remains low, which is exacerbated by increased incidence of weather shocks. Breeding programs have made significant progress with improved (stress-tolerant) varieties for major crops. Full potential however is not utilized: technology diffusion is slow and farmers remain exposed to a multiple of risks. Our main question: How do we increase the adoption of stress-tolerant varieties, while improving agricultural risk management more broadly?